NILAI-NILAI KARAKTER MATEMATIS DALAM PROSES PEMBELAJARAN MELALUI MODEL PEMBELAJARAN YANG BERBASIS KONSTRUKTIVISME - Lusiana Lusiana (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2017)
The purpose of writing this article, want to describe some values of mathematical characters that appear in the implementation of learning mathematics through a model of learning based on kontruktivisme. The learning process that is carried out in the learning of mathematics is very diverse learning model used. Because the learning model used adapted to the goals to be achieved. even the values karakakter who want raised in the process of learning mathematics can we specify and adjusted to the material discussed. The method of writing this article used the method of literature and data used document data from some research results use of constructivism-based learning model in the process of learning mathematics. The problems that will be discussed in this article